IONIZING RADIATION AND ITS BIOLOGICAL EFFECTS - rhaif , Maryam zaman jabbar; Fnkhyr, Najlaa Hamed Anad; a’arebe, Dhuha Adnan Sultan; Oda , Naba’a Jabbar Farhan; Ali, Fatima kareem Mohammad (Journal of Medical Genetics and Clinical Biology, 2024)
Ionizing radiation is a type of energy released by certain atoms in the form of electromagnetic waves or particles. People are exposed to natural sources of ionizing radiation, including those found in soil, water, and plants, and to other man-made sources such as X-ray machines and medical devices. Ionizing radiation has many useful applications, including its uses in areas such as medicine, industry, agriculture, and research. As the use of ionizing radiation increases, so does the potential for health risks if it is not used or contained properly. Acute health effects such as skin burns or acute radiation syndrome can occur when radiation doses exceed very high levels. Exposure to low doses of ionizing radiation can increase the risk of long-term effects, such as cancer. The first chapter discussed the importance of radiation, its sources, types, and methods of protection from it. The second chapter discussed the effects of radiation, including biological effects and their impact on humans. In the third chapter, we discussed in detail how to protect against radiation. Finally, through what we discussed in the research, we reached the most important conclusions and also the most important recommendations